2000
DOI: 10.1002/1522-2683(20000701)21:13<2651::aid-elps2651>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species identification of novelCandida albicans immunogenic proteins by combination of two-dimensional polyacrylamide gel electrophoresis and mass spectrometry

Abstract: We have previously reported the usefulness of two-dimensional gel electrophoresis followed by Western blotting with sera from patients with systemic candidiasis in the detection of the major Candida albicans antigens (Pitarch et al., Electrophoresis 1999, 20, 1001-1010). The identification of these antigens would be useful for the characterization of good markers for the disease, and for the development of efficient diagnostic strategies. In this work we have used nanoelectrospray tandem mass spectrometry to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…(i) Differences between the sequences in the S. cerevisiae and the brewing yeast genome decreased the number of "useful" peptides for the PMF-based identification. (ii) As a consequence of (i), the protein coverage observed was lower than currently published [30,43]. Even if solely one or two peptide masses matched may be enough for a correct identification when the sequence of protein analyzed is in the database [23,48], in our very specific context, our results demonstrated that at least four peptide masses have to be matched to lead to the right identification (Table 5).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…(i) Differences between the sequences in the S. cerevisiae and the brewing yeast genome decreased the number of "useful" peptides for the PMF-based identification. (ii) As a consequence of (i), the protein coverage observed was lower than currently published [30,43]. Even if solely one or two peptide masses matched may be enough for a correct identification when the sequence of protein analyzed is in the database [23,48], in our very specific context, our results demonstrated that at least four peptide masses have to be matched to lead to the right identification (Table 5).…”
Section: Discussionmentioning
confidence: 68%
“…In this present study, the approach used to identify "non-S. cerevisiae" proteins extracted from the industrial strain was different from the one of Humphery-Smith's group but rather closer to those used by Phan-Thanh and Mahouin [30], Pardo et al [43], and Touzet et al [44]. First, we reported only brewing yeast protein identifications based on PMF (MALDI-TOF) and we selected in database only protein sequences of S. cerevisiae which is the reference yeast strain as its whole genome is involved in the constitution of the brewing yeast proteome [25].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations